Reconstructing Corporate Liability for Environmental Pollution Caused by Industrial Waste Under Environmental Protection and Management Law - Jamaat Widyo Pamungkas; Anto Kustanto; Takwim Azami (JURNAL AKTA, 2025)
This study analyzes corporate legal liability for environmental pollution caused by industrial waste based on Law Number 32 of 2009 concerning Environmental Protection and Management. The research focuses on the forms of corporate liability, legal provisions related to liability, as well as sanctions and law enforcement mechanisms. Using a normative juridical design and a descriptive-analytical approach, this study examines primary legal materials in the form of the Environmental Protection and Management Law and secondary legal materials. Descriptive-analytical analysis was conducted to explain legal norms, the relevance of implementation, and the impact of legal practices on the effectiveness of environmental enforcement and protection. The results show that the Environmental Protection and Management Law provide a comprehensive framework with the polluter pays principle, making corporations legal subjects obliged to comply with environmental quality standards and prohibitions on illegal waste disposal. Sanctions can be cumulatively administrative, criminal, and civil, with enforcement mechanisms through inter-agency coordination, central government intervention, and community involvement. However, practical obstacles in the field, such as limited apparatus capacity, weak regulatory harmonization, and low public participation, indicate the need for capacity-building strategies, regulatory harmonization, and integration of community participation to increase legal certainty and the effectiveness of corporate accountability.